Evaluasi Program Pendidikan Kesetaraan Paket C Berbasis Model Stake di PKBM Sabilul Huda (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The aim of this research is to evaluate the evaluation of equality education programs using the stake method. This research used a qualitative approach, and was carried out at PKBM Sabilul Huda which is located at Kp. Tejakalapa, Sukamukti, Kec. Cisayong, Tasikmalaya Regency. The informants in this research were PKBM Sabilul Huda managers, PKBM Sabilul Huda educators, and student representatives. Data were collected using interviews, documentation and documentation and analyzed using the triangulation model. The research results show that management at PKBM Sabilul Huda is quite good from several aspects such as antecedents (supporting factors), transactions (learning processes), and outcomes (results achieved).